Predicting the working time of multi-ply conveyor belt splices in underground mines - Bajda, Mirosław (Wydział Geoinżynierii, Górnictwa i Geologii Politechniki Wrocławskiej, 2024)
Knowledge about the service life of the splices before they are made is extremely valuable in-formation for the users of belt conveyors because having additional technical data about the conveyor and the place of its installation makes it possible to forecast the working time of the joint. The results of calcu-lations of the service life of joints of multiply textile conveyor belts are presented. The calculations were made using a computer program specially created for this purpose, which predicts the service life of the joints before they are made. The program was created due to the implementation of research grant No. PBS3/A2/17/2015 financed by the National Center for Research and Development (NCBiR). The sim-ulation results were compared with the data showing the working time of the joint in actual conditions of its operation in an underground mine. Comparing the simulation results of failure-free operation of joints with accurate data on the operation time of joints in the analyzed mines, it was noticed that the joints could work longer. Depending on the mine, it was from 3 to 8 months. The simulation did not consider sudden phenomena that could occur during the belt and joint operation. It was assumed that the belt operated smoothly, did not run off the conveyor, did not rub against the conveyor structure, etc. Each such phenom-enon shortens its working time. The simulation results also showed that the joint made by hot vulcanization is characterized by a longer working time than the one made by cold gluing.
Mining Science, Vol. 31, 2024, s. 259-274
Keywords: górnictwo; geologia; geoinżynieria; multi-ply textile conveyor belt; conveyor belt splice; splice service life; splice durability